Effects of sugar-sweetened soda on plasma saturated and monounsaturated fatty acids in individuals with obesity: A randomized study - Bajahzer, Mohammed Fahad; Bruun, Jens Meldgaard; Rosqvist, Fredrik; Marklund, Matti; Richelsen, Bjørn; Risérus, Ulf (Frontiers in Nutrition, 2022)
Abstract Background: High carbohydrate, i.e., sugars, intake potentially drives the liver into a lipogenic state leading to elevated plasma fatty acids. Excessive intake of saturated fat and sugar-sweetened soda induces liver fat accumulation, but studying the effect of high intake from sugar-sweetened soda on the de novo lipogenesis (DNL) fatty acids in long-term randomized trials is lacking. Objective: To study the effect of consuming 1L/day of sugar-sweetened soda, semi-skimmed milk (milk), aspartame-sweetened soda or water over 24 weeks on DNL-derived fatty acids (i.e., palmitate (primary outcome), and other saturated and monounsaturated fatty acids) and markers of stearoyl-CoA desaturase activity (SCD1) in plasma phospholipids (PL), cholesteryl esters (CE) and triglycerides (TG). Design and methods: A randomized parallel study was conducted simultaneously at Aarhus University Hospital and Copenhagen University, Denmark, including (n=41) individuals aged 20 to 50 years, with BMI of 26 to 40 kg/m2, and without diabetes. The groups consisted of n=9 individuals in the sugar-sweetened soda, n=10 in the milk, n=11 in the aspartame-sweetened soda, and n=11 in the water. The change at 24 weeks was assessed and compared across the groups using ANCOVA and mixed effects models. Correlations of fatty acids changes with liver fat accumulation (magnetic resonance imaging) was explored. Results: After 24 weeks, the groups differed in the levels of palmitate in PL, oleate in CE and PL, and palmitoleate and SCD1 in all fractions (p<0.05). Compared with water, the relative proportion of palmitate in PL increased approximately 1% during both sugar-sweetened soda (p=0.011) and milk (p=0.006) whereas oleate and palmitoleate increased only during sugar-sweetened soda (CE 2.77%, p<0.001; PL 1.51%, p=0.002, and CE 1.46%, PL 0.24%, TG 1.31% all p<0.001, respectively). Liver fat accumulation correlated consistently with changes in palmitoleate whereas correlations with palmitate and oleate were inconsistent across lipid fractions. Conclusions: Whereas both sugar-sweetened soda and milk increased palmitate in PL, only excess intake of sugar-sweetened soda increased palmitoleate in all lipid fractions and correlated with liver fat. In contrast, isocaloric milk intake did not increase plasma monounsaturated fatty acids. Clinicaltrials.gov identifier: NCT00777647, https://clinicaltrials.gov/ct2/show/NCT00777647